Utilization of electrochemical impedance spectroscopy for monitoring bornite (CU5FeS4) oxidation by Acidithiobacillus ferrooxidans - Bevilaqua, Denise [UNESP]; Acciari, Heloisa Andréa [UNESP]; Arena, Fabiana A. [UNESP]; Benedetti, Assis Vicente [UNESP]; Fugivara, Cecilio Sadao [UNESP]; Tremiliosi Filho, Germano; Garcia Júnior, Oswaldo[UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
In this work, the monitoring of the bacterial and chemical dissolution of bornite was evaluated using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS); the mineral surface was examined using scanning electron microscopy (SEM) and atomic force microscopy (AFM). The analysis of CV results allowed attributing the different peaks observed in both direct and reverse potential scanning to the oxidation of bornite to a secondary covellite and its reduction via different non stoichiometric copper sulphides intermediaries. EIS data for bornite were obtained in control medium up to 78 h of immersion, when a cellular suspension of A. ferrooxidans was added and the experiments continued up to a 192 h of test. The EIS response was different when bacteria were added in the beginning of the test or after some hours of immersion in acid solution. The experiments were performed in different cell configurations and a model of the electrode/electrolyte interface. The correspondent equivalent electrical circuit was used to fit impedance spectra for all studied conditions. A common equivalent circuit used for corrosion processes where anodic (degradation of the mineral) and cathodic (oxygen reduction) reactions occur in parallel, together film and biofilm formation was proposed. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bornite (Cu5FeS4); Acidithiobacillus ferrooxidans; Electrochemical impedance spectroscopy (EIS); Bioleaching